Processes Maintaining Tropopause Sharpness in Numerical Models. Issue 18 (22nd September 2017) - Saffin, L.; Gray, S. L.; Methven, J.; Williams, K. D.
Abstract: Recent work has shown that the sharpness of the extratropical tropopause declines with lead time in numerical weather prediction models, indicating an imbalance between processes acting to sharpen and smooth the tropopause. In this study the systematic effects of processes contributing to the tropopause sharpness are investigated using daily initialized forecasts run with the Met Office Unified Model over a three‐month winter period. Artificial tracers, each forced by the potential vorticity tendency due to a different model process, are used to separate the effects of such processes. The advection scheme is shown to result in an exponential decay of tropopause sharpness toward a finite value at short lead times with a time scale of 20–24 h. The systematic effect of nonconservative processes is to sharpen the tropopause, consistent with previous case studies. The decay of tropopause sharpness due to the advection scheme is stronger than the sharpening effect of nonconservative processes leading to a systematic decline in tropopause sharpness with forecast lead time. The systematic forecast errors in tropopause level potential vorticity are comparable to the integrated tendencies of the parametrized physical processes suggesting that the systematic error in tropopause sharpness could be significantly reduced through realistic adjustments to the model parametrization schemes. Key Points: Tracers of potential vorticity are used to investigate the evolution of tropopause sharpness and reasons for systematic model error The tropopause smooths due to an imbalance between parametrized processes sharpening and the advection scheme smoothing the tropopause Sharpening is weaker, and advective smoothing is more rapid in ridges compared to troughs